Toxicity Profile of IMRT Vs. 3D-CRT in Head and Neck Cancer: A Retrospective Study - Ghosh, Gopa (J Clin Diagn Res, 2016)
INTRODUCTION: Role of radiotherapy in comprehensive management of head and neck cancer for achieving tumour control and organ preservation is now well established and radiotherapy is routinely used in adjuvant setting after surgery, concurrently with chemotherapy or targeted agents and for palliation. Development of linear accelerator with Multileaf Collimator (MLC) have revolutionized radiation delivery techniques, allowing conformal and Intensity Modulated Radiotherapy (IMRT) to deliver highly conformal sculpted radiation dose to a very complex structure with improved sparing of adjoining critical structures like salivary glands, spinal cord, eyes, brainstem and larynx amounting to better therapeutic gain. AIM: This retrospective study was to compare toxicity profile of IMRT with Three Dimensional Conformal Radiotherapy (3D CRT) in head and neck cancer. MATERIALS AND METHODS: Total of 80 patients from January 2013 to July 2015 with proven head and neck cancer who underwent radiotherapy on linac 2300 C/D machine were included in the study, IMRT group and 3D-CRT group comprised of 40 patients each. We have searched patient’s radiotherapy details in record section of our institute and observations were noted down. Patients received 70Gy/35 fractions, Monday to Friday as radical treatment and 60 Gy/30 fractions as adjuvant treatment were included. RESULTS: The 3D-CRT group demonstrated significantly more acute toxic effects compared with the IMRT group in our analysis. Acute Grade 3 or greater toxic effects to the skin occurred in 5 of 40 (12.5%), patients in the 3D-CRT group compared with 3 of 40 (7.5%) patients in the IMRT group. Acute Grade 3 or greater toxic effects to the mucous membranes occurred in 23 of 40 (57.5%) patients in the 3D-CRT group and only 16 of 40 (40%) patients in the IMRT group. Statistically significant dysphagia developed in 34 of 40 (85%), patients in 3D-CRT group compared with 23 of 40 (57.5%) patients in IMRT group, while statistically significant xerostomia developed in 29 of 40 patients in 3D-CRT group (72.5%), compared with18 of 40 (45%) patients in IMRT group. CONCLUSION: In our analysis, IMRT was associated with a significantly lower incidence of Grade 3 or greater xerostomia, acute toxic effects to skin and mucous membranes than 3D-CRT. In addition, compared to 3D-CRT, IMRT had lower rates of Grade 3 or greater mucositis and skin toxicity as well as less feeding tube use during radiotherapy. Our analysis showed potentially less toxicity in patients treated with IMRT in comparision to 3D-CRT.